Barriers and facilitators to cervical cancer screening among under- and neverscreened women in Flanders, Belgium - a qualitative study on community and healthcare providers' perspectives - Bo Verberckmoes; Elien De Paepe; Janne De Vestele; Ana Gama; Ines Keygnaert; Heleen Vermandere; Olivier Degomme (BMC, 2024)
Abstract Background Cervical cancer is detectable and preventable in premalignant stages. In 2013, a population-based cervical cancer screening (CCS) programme was set up in Flanders (Belgium) promoting screening by means of sending reminder letters. Yet, in 2021, only a CCS coverage of 63.6% has been reached, which is just a bare increase since the implementation of the programme (62.7% in 2013) (Jaarrapport 2022, Centrum voor Kankeropsporing (CvKO), 2022; Jaarrapport 2015, Centrum voor Kankeropsporing (CvKO), 2015). Objectives To explore the characteristics of under- and neverscreened women in Flanders and to gain a better understanding of the barriers that prevent these women from attending CCS as well as factors that may facilitate CCS uptake. Methods Twelve in-depth interviews and six focus group discussions were conducted with gynaecologists, general practitioners, community health workers and stakeholders providing support to women belonging to potentially underscreened population groups. Reported barriers and facilitators were subsequently classified using the Socio-Ecological Model (SEM). Finally, a causal loop diagram was constructed to visualise the dynamic interrelations among the barriers and facilitators. Results Stakeholders and healthcare professionals confirm the vulnerability for cervical cancer screening in women with a substance use disorder and women with a migration background. The participation in screening among female sex workers is contingent upon their specific work environment. The group of never- or underscreened women is very heterogeneous and includes many women who are either unaware of CCS or have other priorities. A lack of focus on prevention is the most commonly reported barrier at the healthcare system level. Increasing awareness about cervical cancer (screening) and creating more opportunities for healthcare workers to offer prevention services are the primary facilitators. Conclusion To improve screening participation in Flanders, different screening strategies tailored to a diversity of women are needed.